2023
DOI: 10.1186/s12886-023-02913-5
|View full text |Cite
|
Sign up to set email alerts
|

A pilot clinical study of complex rhegmatogenous retinal detachment treatment via foldable capsular buckle scleral buckling

Abstract: Background To evaluate the feasibility of and identify problems in treating complex rhegmatogenous retinal detachment using foldable capsular buckle scleral buckling. Methods This prospective clinical study enrolled five patients with complex rhegmatogenous retinal detachment treated with foldable capsular buckle scleral buckling at the 988th Hospital of People’s Liberation Army Joint Logistic Force, China. During the 24-week follow-up period, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…However, retinal redetachment occurred in 2 patients, and they needed secondary surgery. Previous studies have reported that the single-operation anatomical success rate of balloon-assisted scleral buckling for RRD ranges from 80% to 100% [1,18,20,22,24,[26][27] . Factors contributing to the failure of the procedure include inadequate buckling, undetected breaks, new breaks discovered after surgery, choroidal detachment, balloon prolapse, another break, inadequate adhesion, break caused by vitreous retraction, proliferative vitreoretinopathy (PVR), etc [19] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, retinal redetachment occurred in 2 patients, and they needed secondary surgery. Previous studies have reported that the single-operation anatomical success rate of balloon-assisted scleral buckling for RRD ranges from 80% to 100% [1,18,20,22,24,[26][27] . Factors contributing to the failure of the procedure include inadequate buckling, undetected breaks, new breaks discovered after surgery, choroidal detachment, balloon prolapse, another break, inadequate adhesion, break caused by vitreous retraction, proliferative vitreoretinopathy (PVR), etc [19] .…”
Section: Discussionmentioning
confidence: 99%
“…The material of FCB is the same as that of FCVB, which is made of FDA-approved pure silicone that has been safely used in the human body for more than 20y with good biocompatibility. The FCB consists of a very thin lumen-shaped balloon and a tube-valve system [24][25] (Figure 1A). In most selected cases, FCB can be used without fixation sutures, cryotherapy, drainage, or traction sutures for external ocular muscles.…”
Section: Introductionmentioning
confidence: 99%